Efeitos do cultivo experimental de peixes em tanques-rede sobre a estrutura da comunidade fitoplanctônica em um braço do reservatório de Salto Caxias, região Sudoeste do Estado do Paraná - Bartozek, Elaine Cristina Rodrigues (2012)
In Brazil, hydroelectric powerplant reservoirs are used for multiple purposes, among them, fish farming in net cages. The present study aimed to evaluate spacial and temporal variations of the abiotic variables, nutrients concentration, trophic state and composition and structure of the phytoplankton community in an arm of Salto Caxias reservoir influenced by experimental fish cultivation in net cages. Samples were bimontly betweem September 2010 and July 2011 at the subsurface of the pelagic zone in four sampling stations, been two of them placed in the arm influenced by the cultivation of 30 net cages and the other two in the cagaless arm. No significant differences were observed for composition, diversity, density and phytoplankton biomass between the treatments. The results of the analisys performed showed only seasonal variations, separating the dry from the rainy period. The values of species richness and Shannon diversity were low during the entire study period. Evenness was high in the dry period and low in the rainy period. Both arms were classified as oligotrophic, possible demonstrating low influence of the net cages in the environment. Phytoplankton density and biomass were higher during the rainy period. The dry period was represented mainly for Bacillariophyceae taxa and the rainy period by Cyanobacteria and Chlorophyceae. Two functional groups (FG) were observed (FG F and K), both of them typical from shallow environments with high transparency water. Variations in the phytoplakton structure seem to have been influenced mainly by the seazonality. The effects of the net cages in the nutrients concentration and phytoplankton structure were probably low, possibly due to the low number of net cages and fishes emploied and environment dinamics, influenced by the inflows of the upstream rivers.